TEACHING AND LEARNING ASPECTS OF TACHERS AND STUDENTS’ MOTIVATION - Filimonova, Liliya (Журнал иностранных языков и лингвистики, 2023)
President of the Republic of Uzbekistan pays more and more attention to the youth development. 2023 year is symbolically called ‘Year of attention to the person and quality education’.